2019
DOI: 10.7717/peerj.7598
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of UV-B radiation on egg size, fertilization, hatching and larval size of sea urchinsStrongylocentrotus intermedius

Abstract: Transgenerational effects are important for phenotypic plasticity and adaptation of marine invertebrates in the changing ocean. Ultraviolet-B (UV-B) radiation is an increasing threat to marine invertebrates. For the first time, we reported positive and negative transgenerational effects of UV-B radiation on egg size, fertilization, hatchability and larval size of a marine invertebrate. Strongylocentrotus intermedius exposed to UV-B radiation showed positive transgenerational effects and adaptation on egg size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…As our knowledge of carryover effects improves, another important consideration is beneficial carryover effects that are derived from processes such as canalisation, reversible phenotypic plasticity, cross‐tolerance and trans‐generational adaptation (Ding et al, 2019; Relyea, 2001). Better knowledge of these processes may allow conservationists to take advantage of these processes.…”
Section: Broader Implications and The Challenges For Conservationmentioning
confidence: 99%
See 3 more Smart Citations
“…As our knowledge of carryover effects improves, another important consideration is beneficial carryover effects that are derived from processes such as canalisation, reversible phenotypic plasticity, cross‐tolerance and trans‐generational adaptation (Ding et al, 2019; Relyea, 2001). Better knowledge of these processes may allow conservationists to take advantage of these processes.…”
Section: Broader Implications and The Challenges For Conservationmentioning
confidence: 99%
“…Importantly, UVR impacts on DNA damage, methylation, chromatin remodelling and gene expression patterns that may have epigenetic consequences affecting survivability of the next generation (De Oliveira et al, 2020; Ho & Burggren, 2010; Rowinski et al, 2020). For example, Ding et al (2019) observed UVR‐induced trans‐generational effects on hatching success and larval size in sea urchins ( Strongylocentrotus intermediusa ). A better understanding of such trans‐generational effects is necessary for better elucidating the long‐term consequences of UVR, and climate change more generally, on amphibian population dynamics (Blaustein et al, 2010).…”
Section: Ultraviolet Radiation and Amphibians: A Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…TGP linked to maternal effects have been observed in S. purpuratus for traits including egg protein content, larval body size, gene expression, and DNA methylation Strader et al, 2020;Strader, Wong, Kozal, Leach, & Hofmann, 2019;Wong, Johnson, Kelly, & Hofmann, 2018;Wong, Kozal, Leach, Hoshijima, & Hofmann, 2019) alongside similar observations in congeneric Strongylocentrotus spp. (Ding et al, 2019) and other urchin genera (Clark et al, 2019;Karelitz, Lamare, Patel, Gemmell, & Uthicke, 2019;Wong & Hofmann, 2021). Maternal conditioning of S. purpuratus to abiotic conditions mimicking coastal upwelling can induce 3 -6x greater DM in offspring larvae relative to the effects of larval development under upwelling (Strader et al, 2020; (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%